Ageism and Technology: The Role of Internalized Stereotypes. - Ivan, Loredana; Cutler, Stephen J. (University of Toronto Quarterly)
Ageist views have typically held that older persons are poor, frail, and resistant to change. One facet of this portrait of the older population has to do with their lower willingness and capability to learn and with their decreased openness to change (Cutler). Many of these ageist views are held by young people, resulting in a bias about the development and designs of different technologies. However, these same views are sometimes shared by older people themselves, resulting in a reluctance to adopt different technologies and the underestimation of their own performance or technology skills (Beckers et al.). In the current work, we analyze the reciprocal relationship between ageist stereotypes and technology, focusing on the implications of negative stereotypes of older people. We emphasize the self-fulfilling prophecy that technology, designed mostly by young people with the youth market in mind, creates prototypes that are more difficult for older people to use and algorithms that often fail to predict the habits, interests, and values of older people (Rosales and Fernández-Ardèvol). We also examine the role of stereotype threat impacting older people's performance and technology adoption; for example, situation-specific anxiety when older people face younger adults who present greater digital skills (Ivan and Schiau).